2011
DOI: 10.21608/jappmu.2011.83412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seaweed Supplementation to Fattening Friesian Steers Rations On: 2- Blood Parameters, Performance and Feed Efficiency

Abstract: Twelve male Friesian steers with average body weight 269+ 9 kg and 15 month of age were used in this study. Steers were distributed into three groups similar in number. The experimental rations were formulated as follows: ration 1 (R1) 81.8% concentrate feed mixture (CFM) + 18.2% clover hay (CH) (control), ration 2 (R2): 81.55% CFM + 18.05% CH + 0.40% seaweed (S) and ration 3 (R3): 81.23% CFM + 17.87% CH + 0.90% S. The results obtained showed that the mean values of blood parameters were not significantly affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Quigley and Poppi (2009) and Panjaitan et al(2010) suggest that increasing level used as a supplement in ruminants is expected to result in proportional improvements in lamb final body weight and average daily gain due to its association with increased rumen microbial crude protein production. Ead et al (2011) found that average daily gain was higher (P>0.05) from 17-18 months when animals were fed rations containing algae.…”
Section: Growth Performancementioning
confidence: 91%
“…Quigley and Poppi (2009) and Panjaitan et al(2010) suggest that increasing level used as a supplement in ruminants is expected to result in proportional improvements in lamb final body weight and average daily gain due to its association with increased rumen microbial crude protein production. Ead et al (2011) found that average daily gain was higher (P>0.05) from 17-18 months when animals were fed rations containing algae.…”
Section: Growth Performancementioning
confidence: 91%